Effectiveness of Ambon Banana Juice for Reducing Blood Pressure Among Hypertension Patients in Indonesia - Marliana, Thika; Pramujiwati, Desi; Samsuni, Samsuni; Heryandi, Rifky (Indonesian Journal of Global Health Research, 2024)
Hypertension has dangerous impacts on health, such as stroke, blurred vision, kidney problems, and a tendency to become irritable. Non-pharmacological therapy for hypertension is lifestyle modification by adjusting eating patterns or diet, such as bananas. This study aims to examine the effectiveness of Ambon banana juice in reducing blood pressure in people with hypertension. Method: This research used a quasi-experimental method with a one-group pre-posttest in Indonesia. This study included 18 participants, sufferers of mild and moderate hypertension, not taking antihypertensive drugs, and not being sick. The instruments used are blood pressure measuring instruments and digital and mercury stethoscopes. The results showed a significant difference between systolic blood pressure before and after administering Ambon banana juice to hypertension sufferers, the Asymp Sig value. (2-tailed) = 0.001, then the p-value = 0.0005 (< 0.05). Apart from that, for diastolic blood pressure, the p-value = 0.000 (< 0.05) means there is a difference between diastolic blood pressure before and after therapy with Ambon banana juice. However, Ambon banana juice reduces diastolic blood pressure in hypertension sufferers. This study highlights that Ambon banana juice effectively reduces blood pressure in hypertensive patients include pre-hypertension and mild hypertension.